Femme Fatale in Korean Drama The Penthouse - Florence Anastasya Tanupribadi (Institute of Research and Community Outreach - Petra Christian University, 2025)
In South Korea, makjang is a genre of Korean drama series that is full of twists and turns. The Penthouse is one of the popular makjang dramas broadcast in 2020. This thesis explores the portrayal of the femme fatale in the popular Korean drama The Penthouse. By examining the characters and narrative used in the series, this study aims to understand how the female antagonists are portrayed in The Penthouse and what strategies they use to achieve their goals. The Penthouse presents its female antagonists as femme fatales who are portrayed as beautiful, powerful, and ambitious women. They also use their manipulation and seduction as their strategies to achieve their goals. The female antagonists in The Penthouse are complex characters who are driven by their ambitions and goals.